Polycystic Ovary Syndrome Is Associated with Fatty Pancreas Disorder: A Case–Control Study in Non-Diabetic Women - Halil Severoglu; Fehmi Ateş; Huseyin Durukan (Journal of Clinical Medicine, 2026)
Background/Objectives: Polycystic ovary syndrome (PCOS) is closely associated with insulin resistance, metabolic syndrome (MetS), and non-alcoholic fatty liver disease (NAFLD); however, whether fatty pancreas disorder is also more common in PCOS remains insufficiently clarified. This study aimed to compare the frequency of hepatic and fatty pancreas disorder and tissue stiffness between women with PCOS and a healthy control group and to determine the relationship of these findings with metabolic and biochemical parameters. Methods: In this retrospective case–control study, 40 women diagnosed with PCOS according to the 2003 Rotterdam criteria and 40 age- and body mass index (BMI)-matched healthy women were evaluated by abdominal ultrasonography and two-dimensional shear wave elastography (2D-SWE) of the liver and pancreas. Four validated non-invasive indices of hepatic steatosis (NAFLD liver fat score, lipid accumulation product [LAP], hepatic steatosis index [HSI], FIB-4, APRI) were calculated and correlated with clinical, anthropometric, and biochemical data. MetS was defined according to International Diabetes Federation (IDF) criteria. Results: Fatty pancreas disorder was detected in 47.5% of PCOS patients versus 17.5% of controls (p = 0.008); hepatic steatosis was found in 37.5% and 15%, respectively (p = 0.04); these differences were observed despite similar age and BMI between groups. LAP and HSI scores were higher in the PCOS group (p = 0.02 and p = 0.005, respectively), as were serum triglyceride and total testosterone levels (p = 0.001 and p = 0.005, respectively). Overall MetS frequency did not differ between the PCOS and control groups (p = 0.61) but was significantly higher among participants with fatty pancreas disorder (p = 0.009) and hepatic steatosis (p = 0.05). Hepatic and pancreatic 2D-SWE values were significantly higher in participants with steatosis than in those without (p = 0.02 and p = 0.04, respectively), and both correlated positively with BMI (p < 0.001 and p = 0.003, respectively). Conclusions: The frequency of fatty pancreas disorder and hepatic steatosis is increased in women with PCOS independent of obesity, and both are associated with a higher frequency of MetS; the association between fatty pancreas disorder and PCOS remained significant in a multivariable analysis adjusted for BMI. Fatty pancreas disorder showed a stronger association with MetS, suggesting that it may serve as an early, low-cost, ultrasound-detectable marker of metabolic risk in PCOS and warrants systematic evaluation alongside hepatic steatosis.